2009
DOI: 10.1080/87559120903155883
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics: Nutrient-Gene Interactions

Abstract: Nutritional research has recently emphasized the role of nutrients on gene expression and regulation. Although not as broadly appreciated, availability of nutrients affects gene expression. The response to a nutrient status seems in many cases to be specific for each genotype and specific nutrient impairment results in altered gene expression, depending on each genotype. Recent literature has suggested that carbohydrates, fatty acids, minerals, and vitamins of all the dietary constituents participate in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Nutrients behave as transcription factors after interacting with a receptor, which binds tightly to DNA and intensely induces gene expression. For instance, as in the case of lac operon, which is by default turned off if lactose is not present in a cell (e.g., bacterial cell) (Siddique et al, 2009). The lacI inhibitor gene binds with promoter region and as a result will not allow RNA polymerase to transcribe, and hence no transcription of DNA takes place.…”
Section: Origin Of Nutrigenomicsmentioning
confidence: 99%
“…Nutrients behave as transcription factors after interacting with a receptor, which binds tightly to DNA and intensely induces gene expression. For instance, as in the case of lac operon, which is by default turned off if lactose is not present in a cell (e.g., bacterial cell) (Siddique et al, 2009). The lacI inhibitor gene binds with promoter region and as a result will not allow RNA polymerase to transcribe, and hence no transcription of DNA takes place.…”
Section: Origin Of Nutrigenomicsmentioning
confidence: 99%
“…The nutrients in our body can interact with our genes. Fundamentally, the nutrient-gene interactions can occur in three ways and could potentially act as drivers of drug-food interactions (Table 6 ) [ 119 , 120 ].…”
Section: Personalized Wellness: Nutrigenomics and Nutrigeneticsmentioning
confidence: 99%
“…Accordingly, in a rapidly changing environment, it is suggested that the adaptation of a DNA sequence to specific changes is a slow process [28]. Thus, the flexibility for rapid adaptation to the environment is therefore facilitated by mechanisms that allow for the modification of a phenotype by epigenetic programming [28].…”
Section: Our Dynamic Genomementioning
confidence: 99%
“…Moreover, it has recently been demonstrated that the epigenome is highly dynamic and changes in response to aging, physical exercise, and nutrients for example [29,32]. Epigenetics is emerging as perhaps the most important mechanism whereby the diet and nutrients can directly affect the genome and thus the modulation of gene expression [28].…”
Section: Gene-nutrient Interactions: Epigenetic Programmingmentioning
confidence: 99%